A Critical review of Mamdouh Adwanâs poetry - Wafeek Sleiteen (دراسات في اللغة العربيّة وآدابها)
This paper carries out an illuminating reading of Mamdouh Adwan’s poetry and his main theoretical principles. Moreover, it uncovers the poet’s general characteristics through studying texts and examples from them, and points out his stylistic methods that establish his poetry between rhetoric and announcement. This leads us to speak about the political and literary qualities that underline his writing and swings between these two sides. In fact, the poet integrates these two elements in one framework. For this purpose, we selected suitable representative examples of such experience to reconstruct this poet’s discourse, find out hidden significant elements and strengthen and guide our reading. Accordingly, we show repeated symbols in Adwan’s poetry and how they are employed, which results in showing the cognitive consequences of such choices and pointing out the hidden insights of this poetic experience.